Beekeeping in coconut smallholdings in Pontian Johor, West Malaysia - Makhdzir, Mardan; Osman, Shamsudin (1980)
In areas under coconut cultivation in Malaysia, wild colonies of Indian honey bees (Apis cerana) are commonly found; provided by the nectar and pollen sources all year round from the palm trees, intermixed orchads and other economic crops. Modern beekeeping has recently been introduced but thus far the efforts are far from success due to lack of skill and knowledge, management problems and acute pestilence. The hot and humid climate has prompted the beekeepers to design and improve hive models, besides utilising available cheap local materials.